Attitude Towards Learning Of Science, Intelligence And Academic Achievement In Science Among Students At The Secondary Level (Journal of Namibian Studies : History Politics Culture, 2022)
The present study investigates the relationship between attitude towards learning of Science, intelligence and academic achievement in Science among students at the secondary level. Survey method is used to select a sample of 618 students at the secondary level. The research tools used are Academic Achievement in Science Attitude towards Learning of Science Scale (Grewal, 1972) and Standard Progressive Matrices (Raven, 1960) The results of the statistical analyses show a significant correlation of attitude towards learning of Science, intelligence  and academic achievement in Science among students at the secondary level. No significant difference was observed among students at the secondary level pertaining to their attitude towards learning of Science, intelligence, and academic achievement in Science among students at the secondary level.